Adolescent Alcohol Use is Predicted by Childhood Temperament Factors Before Age 5, with Mediation Through Personality and Peers. (10th July 2013) - Dick, Danielle M.; Aliev, Fazil; Latendresse, Shawn J.; Hickman, Matt; Heron, Jon; Macleod, John; Joinson, Carol; Maughan, Barbara; Lewis, Glyn; Kendler, Kenneth S.
<x xml:space="preserve">Abstract</x> Background Very few studies chart developmental pathways from early childhood to adolescent alcohol‐related outcomes. We test whether measures of temperament collected from mothers at multiple assessments from 6 months through 5 years predict alcohol‐related outcomes in mid‐adolescence, the developmental pathways that mediate these effects, and whether there are gender differences in pathways of risk. Methods Structural models were fit to longitudinal data from the Avon Longitudinal Study of Parents and Children, an epidemiological sample of pregnant women with delivery dates between April 1991 and December 1992, with children followed longitudinally. Temperamental characteristics were assessed at 6 time points from 6 to 69 months of age. Alcohol use and problems were assessed at age 15.5. Analyses here utilize data from 6, 504 boys and 6, 143 girls. Results Childhood temperament prior to age 5 predicted adolescent alcohol use and problems at age 15.5 years, even after controlling for socio‐demographic factors and parental alcohol problems. In both boys and girls, 2 largely uncorrelated and distinct temperament styles—children who were rated as having consistent emotional and conduct difficulties through age 5, and children who were rated as consistently sociable through age 5—both showed elevated rates of alcohol problems at age 15.5, but via different mediational pathways. In both genders, the association between emotional and conduct difficulties and alcohol problems was mediated through reduced conscientiousness and lower emotional stability. The association between sociability and alcohol problems was mediated through increased extraversion and sensation‐seeking for both genders. Boys also showed mediation for sociability and alcohol outcomes through friendship characteristics, and girls through lower conscientiousness and reduced emotional stability. Conclusions Our findings support multiple pathways to alcohol consumption and problems in adolescence. Some of these pathways are shared in boys and girls, while other risk factors are more salient in one gender or the other.